Review of Methods for Documentation, Management, and Sustainability of Cultural Heritage. Case Study: Museum of King Jan III’s Palace at Wilanów - Tobiasz, Aleksandra; Markiewicz, Jakub; Łapiński, Sławomir; Nikel, Joanna; Kot, Patryk; Muradov, Magomed (Sustainability, 2019)
All countries around the world are blessed with particularly rich cultural heritage. Nowadays, many researchers are exploring different methods for documentation, management, and sustainability of cultural heritage. The aim of this article is to review the state-of-the-art documentation, management, and sustainability techniques in the field of cultural heritage based on the case study in the Museum of King Jan III’s Palace at Wilanów. Various 2D/3D image and range-based methods are discussed demonstrating their applications and drawbacks. The geographical information system (GIS) is presented as a method for management, storage, and maintenance of cultural heritage documentation.